Production of bundled CNTs by floating a compound catalyst in an atmospheric pressure horizontal CVD reactor - Shukrullah, S. (2019)
Although floating catalyst CVD is an economical and flexible technique for production of carbon nanotubes (CNTs), scant information is available on production of bundled CNTs using this technique. In this study, multiwalled carbon nanotubes (MWCNTs) were grown in bundles by cracking ethylene molecules over Fe2O3/Al2O3 compound catalyst in a floating catalyst CVD reactor. The process temperature and catalyst weight were varied from 700 °C to 850 °C and 0.1 g to 0.5 g, respectively. The as-synthesized CNT bundles were characterized for their surface morphology, multi-layered structures, diameter distribution, chemical composition, elemental mapping, and crystallinity. The results showed the formation of CNT forest over Fe2O3/Al2O3 catalyst. The denseness of the forest varied with process temperature and catalyst weight. The product yield varies from 48 to 93, depending on the process temperature and catalyst weight. The maximum yield and crystallinity of nanotubes were reported for process temperature of 800 °C and catalyst weight of 0.3 g. The Raman analysis of the product showed the lowest ID/IG ratio of 0.78 under optimized conditions. The average outer diameter of CNT bundles remained between 240 nm and 550 nm. The outer diameter of individual tubes was measured between 40 nm and 100 nm. © 2019 The Authors